Application of MCAT in Optimizing and Prioritizing Dryland Allocation Based on the Amount of Chemical Fertilizer and Pesticides (A Case Study: Gonbadkavoos County) - B. Raheli namain; S. Mortazavi; A. Salman Mahini (علوم آب و خاک, 2019)
Agriculture production with high quality and adequate income for farmers and the least harmful effects in environment are the main objectives of agriculture optimization. The main objective of this study was ranking, optimization and land allocation of Gonbadkavoos’s Drylands for strategic products such as wheat, barley, oilseed rape‎ and soybean under environment and socio-economic scenarios. Because the available information on fertilizer and pesticide consumption was not sufficient and reliable, this data was collected through face-to-face interviews with farmers. The results showed that some slightly and moderately hazardous pesticides were consumed in study area. In this study, the optimized combination of agriculture products was applied by using the modeling approach and considering environmental and socio-economic aspects in Gonbadkavoos County.‎ This approach uses MCAT software, which is based on multi-criteria techniques and metaheuristic algorithms. The results of the environmental scenario‎ show‎ ed that barley, oilseed rape‎ and soybean, with little difference,‎ had the highest benefit-to-cost ratio and profitability, respectively. The slight difference could be related to the use of fertilizers and pesticides. In the socio-economic scenario, oilseed rape, wheat and barley had the highest benefit-to-cost ratio and land allocation, respectively. The represented approach using the decision support system (MCAT) can help planners to design optimal cropping systems and aid good management of fertilizers and water consumption.